Instrumental and integrative motivation among undergraduate Libyan students of English as a foreign language - Zanghar, Ahmed, author; Delahunty, Gerald, advisor; Ehlers-Zavala, Fabiola, committee member; Feller, Rich, committee member (Colorado State University. Libraries, 2012)
The study examines instrumental and integrative motivations among undergraduate Libyan students of English as a foreign language (EFL). It investigates whether EFL Libyan students are instrumentally or integratively motivated to study English. The study also looks at the relationship between EFL Libyan students' motivation and their achievement in English. Forty Libyan students studying English as a foreign language at the College of Arts Bani Walid, Libya, participated in the study. The participants are in different levels of their four-year university program as ten students were chosen from each year. All of the participants completed a questionnaire that included 14 items reflecting their instrumental and integrative motivations for studying English. The questionnaire data was analyzed using SPSS version 21. The findings of the study showed that EFL Libyan students were highly instrumentally as well as integratively motivated to study English, and they their integrative motivation appeared to be a little higher than their instrumental one. These unusual results of the study were attributed to the Libyan students' interest in knowing more about the English-speaking peoples and learning about their societies and cultures, and that was due to the strong positive attitude Libyan students have had towards them. The findings also revealed that there was no relationship between the Libyan students' motivation and their achievement in English as a foreign language.
Keywords: language learning; motivation